2014
DOI: 10.5195/jyd.2014.59
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effectiveness of the Leave No Trace PEAK Program

Abstract: The Leave No Trace Center for Outdoor Ethics developed the Promoting Environmental Awareness in Kids (PEAK) program to teach children the seven Leave No Trace principles. The purpose of this study was to assess the effectiveness of the PEAK program. A significant increase was found between the pre-test (M = 3.41, SD = .34) and the post-test (M = 3.61, SD = .36) with the post-test scores being significantly higher, F(1, 140) = 11.15, p

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…This program measured the impact of BFPB activities facilitated in an afterschool program. Previous studies have explored the impact of LNT's Promoting Environmental Awareness in Kids (PEAK) program (Miller et al, 2014). Results indicated that PEAK effectively introduced youth to the 7 Principles of Leave No Trace.…”
Section: Discussionmentioning
confidence: 99%
“…This program measured the impact of BFPB activities facilitated in an afterschool program. Previous studies have explored the impact of LNT's Promoting Environmental Awareness in Kids (PEAK) program (Miller et al, 2014). Results indicated that PEAK effectively introduced youth to the 7 Principles of Leave No Trace.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the long-term effects of these knowledge gains can vary. Youth participating in a Leave No Trace programs increased their knowledge immediately following the program; however, retention after 8 months significantly decreased (Miller et al, 2014).…”
Section: Journal Of Outdoor Recreation Education and Leadershipmentioning
confidence: 95%
“…Previous studies suggest that those who have more pro-social values or collective good values are more likely to engage in PEB; similarly, those who hold ecological worldviews more in line with ecocentrism versus anthropocentrism are more likely to engage in PEB (De Groot & Steg, 2008;Cameron et al, 1998, van Riper & Kyle, 2014. While worldviews and values are culturally rooted and highly invariable, education and outreach efforts (e.g., interpretation programs focused on children such as Junior Rangers, extended school programming, and immersive activities), show good success in influencing environmental issues and concerns in the long-term (Miller et al, 2014;Powell et al, 2018). The holistic emphasis on emotions, worldviews, and attitudes is slowly emerging in interpretive practice, as opposed to a reductionist emphasis on education (Gilson & Kool, 2019).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Among climbing populations, those people identifying as females and people of color sometimes showed greater knowledge of LNT than comparison categories (Maples et al, 2022). Perceptions and self-reported behaviors related to LNT have also been explored with youth (Miller et al, 2014), generally finding that education can influence attitudes and self-reported behaviors of children.…”
Section: Leave No Tracementioning
confidence: 99%